Targeted immunotherapies for Graves’ thyroidal & orbital diseases - Lee, Alan Chun Hong; Kahaly, George J. (Frontiers in Immunology, 2025)
BackgroundGraves’ hyperthyroidism and its associated Graves’ orbitopathy are common autoimmune disorders associated with significant adverse health impact. Current standard treatments have limitations regarding efficacy and safety, and most do not specifically target the pathogenic mechanisms. We aim to review the latest development of targeted immunotherapies in these two closely related disorders.SummaryTargeted immunotherapies of Graves’ hyperthyroidism have recently demonstrated clinical efficacy in early phase clinical studies. They include rituximab, an anti-CD20 monoclonal antibody which causes rapid B cell depletion; ATX-GD-59, an antigen specific immunotherapy which restores immune tolerance to thyrotropin receptor; iscalimab, an anti-CD40 monoclonal antibody which blocks the CD40-CD154 co-stimulatory pathway in B-T cell interaction; and K1-70, a thyrotropin receptor blocking monoclonal antibody. Furthermore, there have been major therapeutic advances in the management of Graves’ orbitopathy. Mycophenolate has a dual mechanism of action both inhibiting the proliferation of activated B & T cells as well as the mammalian target of rapamycin growth intracellular pathway. Rituximab appears to be effective in active disease of recent onset without impending dysthyroid optic neuropathy. Both tocilizumab (anti-interleukin 6 receptor monoclonal antibody) and sirolimus (mammalian target of rapamycin inhibitor) showed promise in glucocorticoid resistant active disease. Teprotumumab, an anti-insulin-like growth factor-1 receptor monoclonal antibody, demonstrated remarkable all-round efficacy across a wide disease spectrum. Linsitinib, a dual small molecule inhibitor of insulin-like growth factor-1 receptor and insulin receptor, displayed significant proptosis reduction in its phase 2b/3 study. Finally, Batoclimab, an anti-neonatal fragment crystallizable receptor monoclonal antibody, which blocks recycling of pathogenic thyrotropin receptor antibody, showed promising signals for significant proptosis reduction, disease inactivation, overall response, and improvement of quality of life.ConclusionTherapeutic advances will continue to optimize our management of Graves’ hyperthyroidism and its associated orbitopathy in an effective and safe manner.